2020
DOI: 10.21203/rs.2.17246/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Economic burden and mental health of primary caregivers of perinatally HIV infected adolescents from Kilifi, Kenya

Abstract: Background: Eighty per cent of perinatally HIV infected (PHI) adolescents live in sub-Saharan Africa (sSA), a setting also characterized by huge economic disparities. Caregiving is crucial to the management of chronic illness such as HIV/AIDS, but the economic costs and mental disorders borne by caregivers of PHI adolescents often go unnoticed. In this study, we evaluated economic costs, coping strategies and association between economic cost and mental health functioning of caregivers of perinatally HIV infec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Similar to findings from other developing countries, having a professional job relative to subsistence farmers (many of whom are likely to be unemployed) was associated with improved overall HRQoL [54]. Arguably, individuals in formal employment are more likely to have higher educational level, enjoy higher wages and better working conditions and work environments compared to those without professional employment, thus less likely impacted by high caregiving burden (as may be the case for carers of adolescents living with HIV [49]), hence the improvement in their HRQoL. Better socioeconomic status has long been associated with good health outcomes in the literature [15].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Similar to findings from other developing countries, having a professional job relative to subsistence farmers (many of whom are likely to be unemployed) was associated with improved overall HRQoL [54]. Arguably, individuals in formal employment are more likely to have higher educational level, enjoy higher wages and better working conditions and work environments compared to those without professional employment, thus less likely impacted by high caregiving burden (as may be the case for carers of adolescents living with HIV [49]), hence the improvement in their HRQoL. Better socioeconomic status has long been associated with good health outcomes in the literature [15].…”
Section: Discussionsupporting
confidence: 63%
“…Our observation could be further explained by the significant economic burden that caregivers of adolescents living with HIV are likely to face in their caregiving roles. Indeed, a recent cross-sectional study in the same study setting documented significant economic burden (especially for transportation and medication costs) among caregivers of perinatally HIV infected adolescents [49]. However, it could be that some of the adult carers are HIV uninfected and yet taking care of adolescents living with HIV or even vice-versa whereby a carer living with HIV is taking care of PHEU adolescent who poses fewer challenges, he/she (adolescent) is disease-free.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported the prevalence of depression among caregivers ranging from 10.7% among carers of perinatally HIV infected adolescents in Kenya (Katona et al, 2020), 12.7% among spouse carers of HIV infected individuals in India (Ghale et al, 2015), 48.3% among carers of HIV infected children in Nigeria (Ogbonna et al, 2019) and 62% and 34% among carers of Status-Naïve paediatric patients in Haiti and the Dominican Republic, respectively (Beck-Sague et al, 2015). In all these studies, the prevalence of depression was higher among female carers and those from low socio-economic homes.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly caregivers, for instance, often stretch state pension grants to meet these needs [ 31 ]. Oftentimes caregivers have to resort to borrowing or selling essential resources to cope with their economic burden [ 29 ]. These households are thus economically vulnerable and the children living in them have the heightened risk of being malnourished [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to tending to the special needs of ALHIV (e.g. adherence, clinic visits, transport costs, nutrition) [28,29], primary caregivers are also challenged with looking after the basic needs of entire households [29][30][31]. Elderly caregivers, for instance, often stretch state pension grants to meet these needs [31].…”
Section: Introductionmentioning
confidence: 99%